Exploring the Gendered Space in Atwood’s The Handmaid’s Tale through Baudrillard’s Simulacrum and Simulation - ABI, Nouha; Selt, Djihad Afaf (Faculty of Letters and Foreign Languages Department of English, 2017)
This work sheds light on the interplay of both: physical and mental spaces linking them to the power relations embedded in a given space wherein power is imposed by the state to control its inhabitants, namely women. The present dissertation, also, consists a study of manipulation of spaces that creates a gendered one in which women are considered as inferiors. It further aims at highlighting the fact that space may be produced through numerous means along with the Panopticon architecture. In this concern, this work is an attempt to manifest how Margaret Atwood’s novel The Handmaid’s Tale presents a fictional gendered space that is created through “simulacrum”. It further investigates how this gendered space –that women are relegated to-imposes a high surveillance on their behaviors and minds to oppress them and subjugate their bodies, considering them mere child-bearing machines